Bilateral changes in IL-6 protein, but not in its receptor gp130, in rat dorsal root ganglia following sciatic nerve ligature - Brázda, Václav; Klusáková, Ilona; Svízenská, Ivana; Veselková, Zuzana; Dubový, Petr (Cellular and molecular neurobiology, 2009)
Local intracellular signaling cascades following peripheral nerve injury lead to robust axon regeneration and neuropathic pain induction. Cytokines are classic injury-induced mediators. We used sciatic nerve ligature (ScNL) to investigate temporal changes in IL-6 and its receptor gp130 in both ipsilateral and contralateral lumbal (L4-L5) dorsal root ganglia (DRG). Rats were operated aseptically on unilateral ScNL and allowed to survive for 1, 3, 7, and 14 days. Immunohistochemistry and Western blot analysis were used to determine levels of IL-6 and gp130 in DRG. A distinct increase in immunostaining for IL-6 was found in the neuronal cell bodies of sections through both ipsilateral and contralateral DRG at 1 and 3 days after operation. After 7 and 14 days, the DRG sections displayed only a moderate elevation in immunostaining when compared with sections of naïve DRG. The levels of IL-6 protein increased in both ipsilateral and contralateral lumbal DRG following peripheral nerve injury. The elevation of IL-6 protein was significant in both ipsilateral and contralateral DRG 1, 3, 7, and 14 days after operation. On the other hand, the levels of gp130 receptor did not change significantly. The data provide evidence for changes in IL-6 levels not only in the DRG associated with the damaged nerve but also in those unassociated with nerve injury during the experimental neuropathic pain model.
Keywords: cytokinový receptor gp130; western blotting; Cytokine Receptor gp130; spinální ganglia; Interleukin-6; měření bolesti; nervus ischiadicus; imunohistochemie; Sciatic Nerve; krysa rodu Rattus; Blotting, Western; Animals; ženské pohlaví; Immunohistochemistry; interleukin-6; zvířata; Rats; Ganglia, Spinal; Female; Pain Measurement